TRANSPLACENTAL EFFECTS OF ANESTHETICS ON FETUSES IN SMALL ANIMALS DURING OBSTETRIC INTERVENTIONS (International Seven Journal of Multidisciplinary, 2025)
Objective: To evaluate the effects of anesthetics used in cesarean sections of small animals, comparing the advantages and disadvantages of inhalational and intravenous anesthetic protocols, considering postoperative recovery, maternal cardiovascular stability, fetal safety, and neonatal viability. Anesthesia in pregnant females is a challenging field, where the choice of anesthetic must minimize risks to both the mother and the fetus due to the physiological particularities of pregnancy and placental transfer. This study was based on a literature review encompassing scientific articles and experimental studies on the transplacental effects of anesthetics, focusing on protocols used in cesarean sections. The findings indicate that intravenous anesthesia, with agents such as propofol, promotes faster recovery and lower placental transfer, while inhalational anesthesia, such as isoflurane, offers precise control during longer procedures but may result in greater fetal depression. Combined protocols and the use of local anesthesia are increasingly recommended to minimize risks to fetal health. It is concluded that the choice of anesthetic protocol should be carefully tailored to the patient's clinical condition, the type of obstetric procedure, and fetal safety.